2022
DOI: 10.3390/polym14020247
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dimethacrylate Monomer on the Polymerization Efficacy of Resin-Based Dental Cements—FTIR Analysis

Abstract: The degree of polymerization for dimethacrylate resin-based materials (BisGMA, TEGDMA, UDMA, HEMA) ranges from 55 to 75%. Literature data indicate that polymerization efficacy depends, among other factors, on the type of methacrylate resin comprising the material. The aim of this study was to evaluate the polymerization efficacy of four dental cement materials characterized by different polymerization mechanisms using FTIR analysis. In the present study, the FTIR method was adopted to analyze the degree of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…After hydrolysis of PCA3 in DMSO/HCl for 6 h, acetal protons disappeared, but aldehyde proton was observed at about 9.7 ppm, indicating that CA could release from the hydrolytic degradation of PCA3. Figure D displays the FTIR spectrum of PCA3, and valence N–H, CO, and N–C vibrations occurred at peak positions about 2953, 1733, and 1046 cm –1 , respectively. , To further investigate the effect of polymer molecular weights on its antimicrobial activities, four kinds of PCA with different molecular weights were prepared. The average molecular weights were 3144 g/mol (PCA1), 4604 g/mol (PCA2), 6351 g/mol (PCA3), and 17478 g/mol (PCA4), respectively, and polydispersity was about 1.2 (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…After hydrolysis of PCA3 in DMSO/HCl for 6 h, acetal protons disappeared, but aldehyde proton was observed at about 9.7 ppm, indicating that CA could release from the hydrolytic degradation of PCA3. Figure D displays the FTIR spectrum of PCA3, and valence N–H, CO, and N–C vibrations occurred at peak positions about 2953, 1733, and 1046 cm –1 , respectively. , To further investigate the effect of polymer molecular weights on its antimicrobial activities, four kinds of PCA with different molecular weights were prepared. The average molecular weights were 3144 g/mol (PCA1), 4604 g/mol (PCA2), 6351 g/mol (PCA3), and 17478 g/mol (PCA4), respectively, and polydispersity was about 1.2 (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Low conversion reduces the biocompatibility of the material due to the increased leaching of unbound molecules 9 . The present research used FTIR spectroscopy because this technique is known to provide more reliable results and is widely used to determine the DC from the C0.28em=0.28emC$C\; = \;C$ bond vibrations measured before and after polymerization 25 . Light‐cured dental composites typically show limited conversion, with DC values ranging from 40% to 80% 12 .…”
Section: Discussionmentioning
confidence: 99%
“…9 The present research used FTIR spectroscopy because this technique is known to provide more reliable results and is widely used to determine the DC from the C = C bond vibrations measured before and after polymerization. 25 Light-cured dental composites typically show limited conversion, with DC values ranging from 40% to 80%. 12 The degree of polymerization for AG showed lower values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to the lower concentration of the additives used in the current study compared to the previous studies. The ability of a material to polymerize upon chemical activation is also essential for core build-up materials to promote adequate polymerization in the deep cavity where light transmission is limited [ 56 ]. The results showed that all experimental materials exhibited similar DC upon self-curing regardless of the level of additives.…”
Section: Discussionmentioning
confidence: 99%